Mitochondrial genome of Macrostemum floridum (Trichoptera). Issue 4 (3rd April 2021) - Qin, Hong-lin; Zhong, Xi-fa; Li, Yi-min; Huang, Jing-cai; Wang, Hong; Wang, Yu-jun
Abstract: Trichoptera are a group of the benthic organism, almost all of which live in water during their life cycle. Trichoptera usually develop through egg, larva, pupa, and moth stages. In its larval stage, Trichoptera usually live in water and are often called the caddisfly. In this study, the mitochondrial genome of Macrostemum floridum was analyzed. The total length of the mitochondrial genome is 15, 424 bp and consists of 13 protein-coding genes, 22 tRNA genes, 2 rRNA genes, and one control region. The genome has a typical mitochondrial gene sequence of Trichoptera. Phylogenetic analysis of the mitochondrial genomes of 23 species of Trichoptera and Lepidoptera showed that M. floridum forms a monophyletic group with other species of Lepidoptera.